2016
DOI: 10.1042/cs20160203
|View full text |Cite
|
Sign up to set email alerts
|

Urea, a true uremic toxin: the empire strikes back

Abstract: Blood levels of urea rise with progressive decline in kidney function. Older studies examining acute urea infusion suggested that urea was well-tolerated at levels 8-10× above normal values. More recent in vitro and in vivo work argue the opposite and demonstrate both direct and indirect toxicities of urea, which probably promote the premature aging phenotype that is pervasive in chronic kidney disease (CKD). Elevated urea at concentrations typically encountered in uremic patients induces disintegration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 94 publications
3
60
0
6
Order By: Relevance
“…Older studies suggested the non-toxicity of high blood urea concentration after acute infusion, but now there are evidences of direct and indirect toxicities of chronically high urea levels, inducing alterations of gut epithelial barrier allowing passage of bacterial toxins into the blood causing systemic inflammation and activating protein carbamylation reaction where isocyanic acid (from urea catabolism) alters the structure and function of proteins in the body. Carbamylation is linked with renal fibrosis, atherosclerosis, and anemia, thereby increasing the CV risk in ESRD patients [21,22] . Intensification of hemodialysis therapy in renal replacement therapy patients, promotion of low-protein diets in CKD patients, could help maintain low levels of plasma urea and reduce carbamylate protein concentration by reducing the CV risk [23] .…”
Section: Protein Carbamylationmentioning
confidence: 99%
“…Older studies suggested the non-toxicity of high blood urea concentration after acute infusion, but now there are evidences of direct and indirect toxicities of chronically high urea levels, inducing alterations of gut epithelial barrier allowing passage of bacterial toxins into the blood causing systemic inflammation and activating protein carbamylation reaction where isocyanic acid (from urea catabolism) alters the structure and function of proteins in the body. Carbamylation is linked with renal fibrosis, atherosclerosis, and anemia, thereby increasing the CV risk in ESRD patients [21,22] . Intensification of hemodialysis therapy in renal replacement therapy patients, promotion of low-protein diets in CKD patients, could help maintain low levels of plasma urea and reduce carbamylate protein concentration by reducing the CV risk [23] .…”
Section: Protein Carbamylationmentioning
confidence: 99%
“…Conversely, abundance decreased for urea [Fig. S4(b)], a known marker of aging which can cause cardiovascular disease, 35,36 and for branched-chain (valine, leucine, and isoleucine) and other amino acids (threonine, phenylalanine, tyrosine, and tryptophan) in VincHE flies [Fig. S4(c)].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, CKD affects red blood cell and platelets that are activated and produce reactive oxygen species, which in turn activates intracellular redox enzymes, for example, superoxide dismutase, catalase, glutathione peroxidase, transferases, and glutathione reductase [6], showing and increased redox imbalance in platelets and red blood cells of CKD patients [5,6,[18][19][20][21]. Markers of protein and lipid peroxidation, for example, malondialdehyde (MDA/TBARS), advanced glycation end products including pentosidine [7,8], advanced oxidation protein products [1,5] are also altered in CKD; however, to date, there are no redox markers that are readily used in the point-of-care testing.…”
Section: Discussionmentioning
confidence: 99%